2023
DOI: 10.12740/pp/onlinefirst/149297
|View full text |Cite
|
Sign up to set email alerts
|

Catatonic syndrome during COVID-19 - a case study

Abstract: Katatonia jest stanem neuropsychiatrycznym obejmującym jakościowe zaburzenia psychomotoryczne i wolicjonalne. Jako jednostka nozologiczna została ujęta w międzynarodowych klasyfikacjach chorób - ICD-10 i DSM-5, jednak kryteria diagnostyczne znacznie różnią się pomiędzy tymi klasyfikacjami. COVID-19 jest chorobą zakaźną obejmującą przede wszystkim układ oddechowy, czasami również inne narządy. W literaturze istnieją pojedyncze doniesienia dotyczące współistnienia COVID-19 z katatonią. Opisywany przypadek dotyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Case reports have reported success with mirtazapine (Yeh et al, 2010) and clomipramine (Barroso Cañizares et al, 1999) in the maintenance treatment of periodic catatonia in patients with depressive disorder (Yeh et al, 2010). In another case report, authors reported the effectiveness of fluoxetine (20 mg/day) and fluphenazine in the maintenance treatment of periodic catatonia in a patient with schizoaffective disorder (Białek and Jarema, 1999). Case reports or series have reported the role of lamotrigine (Konstantinou et al, 2021) and carbamazepine (Padhy et al, 2011) in the maintenance treatment of periodic catatonia.…”
Section: Periodic Catatoniamentioning
confidence: 99%
“…Case reports have reported success with mirtazapine (Yeh et al, 2010) and clomipramine (Barroso Cañizares et al, 1999) in the maintenance treatment of periodic catatonia in patients with depressive disorder (Yeh et al, 2010). In another case report, authors reported the effectiveness of fluoxetine (20 mg/day) and fluphenazine in the maintenance treatment of periodic catatonia in a patient with schizoaffective disorder (Białek and Jarema, 1999). Case reports or series have reported the role of lamotrigine (Konstantinou et al, 2021) and carbamazepine (Padhy et al, 2011) in the maintenance treatment of periodic catatonia.…”
Section: Periodic Catatoniamentioning
confidence: 99%